Doing Poor in AmeriCorps: How National Service Members Deal With Living Below the Poverty Line - Ceresola, Ryan (Qualitative Sociology Review, 2015)
Many young AmeriCorps members enter a post-college lifestyle of food stamps, social services, and living below the poverty line. Using Simmel’s (1965) concept of poverty as a social category one is put into, and West and Fenstermaker’s (1995) concept of class as something one “does,” this paper looks at the AmeriCorps program, to examine how members “do poor.” In 22 in-depth interviews with a diverse sample of AmeriCorps members, I detail a member’s “typical” experience with poverty: first, encountering themselves in poverty, then working to disassociate themselves from having a “poor” identity, and, finally, still maintaining the positive experiences associated with their service.